2015
DOI: 10.1002/sca.21208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of MTAD and conventional irrigation agents on apical leakage and push‐out bond strength of root canal filling

Abstract: The aim of this study was to evaluate the effect of MTAD (a mixture of tetracycline isomer, an acid, and a detergent) and conventional irrigation agents on the apical leakage and push-out bond strength of root canal filling and to correlate the apical leakage and push-out bond strength. Root canals of 120 maxillary central incisors were prepared with a ProTaper file up to F3 and distributed to six groups. Saline, 1% NaOCl, 17% EDTA, 17% EDTA/1% NaOCl, and 2% chlorhexidine (CHX) solutions were used between each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The results revealed that, a statistically significant difference in the mean push out bond strength among group III (NaOCl) and control group (saline) was present, where the samples treated with NaOCl showed higher values. This finding was in consent with a previous study which concluded that the push-out bond strength of AH plus sealer when the specimens irrigated with NaOCl was higher than when irrigated with saline (34) .…”
Section: Discussionsupporting
confidence: 91%
“…The results revealed that, a statistically significant difference in the mean push out bond strength among group III (NaOCl) and control group (saline) was present, where the samples treated with NaOCl showed higher values. This finding was in consent with a previous study which concluded that the push-out bond strength of AH plus sealer when the specimens irrigated with NaOCl was higher than when irrigated with saline (34) .…”
Section: Discussionsupporting
confidence: 91%
“…The smear layer is an iatrogenic layer, generated on dentinal surfaces, primarily consist of inorganic particles of calcified tissue and organic material including bacteria, blood cells, necrotic tissue, pulp tissue and odontoblastic processes. (2,3,6) Therefore, removal of this layer is an essential step, as its presence prevents the penetration of root canal materials to root canal surfaces. Sodium Hypochlorite (NaOCl) is the most widely used irrigating solution, because of its an antibacterial activity and the capacity to rapidly dissolve necrotic tissue, vital tissue of the pulp, and the organic debries of dentin and biofilms.…”
Section: Introductionmentioning
confidence: 99%